World literature studies 2. Vol. 7, Outstanding romanian personalities in world literature and literature studies (Colloquia Comparativa Litterarum, 2025)
World literature studies 2, vol. 7, Outstanding Romanian Personalities in World Literature and Literature Studies. (Eds.) Libuša Vajdová, Andrei Terian. Bratislava, Institute of World Literature, SAS, 2015.